Gold Electroplating as a Tool for Assessing the Conductivity of InP Nanostructures Fabricated by Anodic Etching of Crystalline Substrates. Issue 4 (1st January 2017) - Monaico, E. V.; Tiginyanu, I. M.; Ursaki, V. V.; Nielsch, K.; Balan, D.; Prodana, M.; Enachescu, M.
Abstract : Electroplating is shown to represent a simple and effective tool for assessing the conductivity of InP nanostructures fabricated by electrochemical etching of InP wafers. A mixture of nanowalls, nanowires and nanobelts was fabricated by anodic etching of crystalline bulk n -InP with free electron concentration of 1.3 × 10 18 cm −3 under applied voltage of 13 V. We found that electroplating of Au occurs differently on these three nanostructures under identical electroplating conditions. A monolayer of densely packed Au nanodots with the diameter of around 20 nm is deposited on nanowires, while the density of Au nanodots deposited on nanowalls proves to be much smaller. At the same time no electroplating occurs on nanobelts. The evidenced distinctive features of electroplating processing are determined by different electrical conductivities of InP nanostructures. The produced materials are characterized by scanning electron microscopy (SEM), high-resolution scanning transmission electron microscopy (HR-STEM), electron nano-diffraction, selected area electron diffraction (SAED), and energy dispersive X-ray analysis (EDAX).